2019
DOI: 10.3390/en12132554
|View full text |Cite
|
Sign up to set email alerts
|

FACTS Providing Grid Services: Applications and Testing

Abstract: The role of flexible alternating current transmission systems (FACTSs) in the provision of grid services is becoming increasingly important, due to the massive integration of intermittent renewable energy sources, energy storage systems, and the decommissioning of thermal plants. A comprehensive literature review of grid services offered by FACTS is performed, focusing on the different grid services that they can provide, such as power flow control, reactive power control, voltage control, power quality improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 97 publications
(157 reference statements)
0
34
0
Order By: Relevance
“…FACTS controller can be installed to improve electric network performance [6]. Moreover, these devices can be used to mitigate the deleterious effects of wind power systems on the electric network, and thus, can be used to increase their penetration level [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…FACTS controller can be installed to improve electric network performance [6]. Moreover, these devices can be used to mitigate the deleterious effects of wind power systems on the electric network, and thus, can be used to increase their penetration level [7].…”
Section: Introductionmentioning
confidence: 99%
“…The capability of FACTS controller in improving the network performance depends mostly on their sizes and locations [8]. Therefore, the proper installation of a FACTS controller at different locations in the network will give different results in terms of network loadability increase [9], loss reduction [6,10], static voltage stability enhancement [11], voltage profile improvement [12], available transfer capability improvement [13] and total generation fuel cost reduction [14] and Congestion management [15]. From the literature survey, it is found that many researchers have suggested different methods to find optimum allocations of FACTS controller for optimization of one or two objectives with or without the presence of renewable energy.…”
Section: Introductionmentioning
confidence: 99%
“…The increase of power quality problems might have an adverse impact on steady state and dynamic stability, limited transmission capacity, and congestion of lines. Therefore, Flexible Alternating Current Transmission Systems (FACTS) have been widely used to improve power grid dynamic and static behavior, providing greater operating flexibility and better utilization [1].…”
Section: Introductionmentioning
confidence: 99%
“…FACTS technology has increasingly drawn wide attention regarding the power quality of the government [6,7]. The power flow controller (PFC) scheme has been adopted to the TPSS [8], for example, by way of the railway static power conditioner (RPC) and co-phase TPSS.…”
Section: Introductionmentioning
confidence: 99%